2004
DOI: 10.1128/jb.186.21.7175-7185.2004
|View full text |Cite
|
Sign up to set email alerts
|

The N Terminus of MinD Contains Determinants Which Affect Its Dynamic Localization and Enzymatic Activity

Abstract: MinD is involved in regulating the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Key domains previously shown to be crucial for Min protein function and dynamics in E. coli were identified in all three predicted S. elongatus structures. MinD possessed a highly conserved N-terminal Walker Atype ATPase domain, Switch I and Switch II domains for binding MinC, and key residues L48, E53, and N222 (L48, E53 and N213 in S. elongatus) important for interaction with MinE (Zhou and Lutkenhaus, 2004;Szeto et al, 2004;Zhou et al, 2005) (Supporting Information Fig. 1C) (Hu and Lutkenhaus, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Key domains previously shown to be crucial for Min protein function and dynamics in E. coli were identified in all three predicted S. elongatus structures. MinD possessed a highly conserved N-terminal Walker Atype ATPase domain, Switch I and Switch II domains for binding MinC, and key residues L48, E53, and N222 (L48, E53 and N213 in S. elongatus) important for interaction with MinE (Zhou and Lutkenhaus, 2004;Szeto et al, 2004;Zhou et al, 2005) (Supporting Information Fig. 1C) (Hu and Lutkenhaus, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…All Ng-MinE constructs were prepared using a slightly modified version of the previously published protocol (38). Briefly, one colony of freshly transformed BL21(DE3) was used to inoculate 50 mL of M9 minimal media containing 50 µg/mL kanamycin and 0.1% (w/v) 15 N-labeled ammonium chloride and 0.3% (w/v) glucose (either U- 13 C or natural abundance) as the sole nitrogen and carbon sources, respectively. The culture was grown overnight at 37 °C and used to inoculate 1 L of the same minimal media which was induced with 0.4 mM isopropyl β-D-thiogalactopyranoside when the OD 600 reached 0.6-0.8.…”
Section: Methodsmentioning
confidence: 99%
“…Backbone 15 N, 1 H N , 13 C R , 13 C β , and 13 CO chemical shift assignments were made on the wild-type Ng-MinE at pH 9.5 based on HNCACB, CBCA(CO)NH, HNCA, HN(CO)-CA, and HNCO experiments, and amide proton assignments were confirmed with a 15 N-edited NOESY utilizing a 100 ms mixing time (41,42). Protected regions were mapped onto the Ec-TSD structure (37; PDB accession number 1EV0), and figures were rendered in MolMol (43).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Escherichia coli, it has been shown that oscillation rates that are too slow can inhibit normal cell division, giving rise to elongated rods (11), whereas oscillation rates that are too fast fail to prevent division at the cell poles (4), leading to the generation of achromosomal minicells that cannot undergo further propagation (12). The chemical engine that drives this coordinated oscillation of Min proteins from pole to pole is powered by MinD-catalyzed hydrolysis of ATP (13,14), which is stimulated by interactions with MinE once MinD has bound to the cell membrane in a dimeric state (15)(16)(17)(18)(19). ATP hydrolysis stimulates the release of Min proteins from the cell membrane (19,20), freeing them to diffuse through the cytoplasm to establish a new zone that is inhibitory to formation of the cytokinetic septum at the opposite side of the cell.…”
mentioning
confidence: 99%